Feasibility of point-of-care ultrasound during the emergency department triage: a prospective cohort study - Enrici Baion, Davide; Schettino, Chiara; Vita, Lara; Luison, Deborah; Caprioli, Stefania; Lombardo, Matteo; La Ferrara, Alberto; Locascio, Francesca; Galluzzo, Emanuela; Ciampi, Vittoria; Ianiro, Aurora; Maserin, Davide; et al. (The Ultrasound Journal, 2025)
Background: The primary aim of this study was to evaluate the feasibility of adding point-of-care ultrasound (POCUS) during the Emergency Department (ED) triage process. This prospective study enrolled two cohorts of adult patients presenting to the ED for a selected group of acute symptoms, previously selected on the basis of the presumed utility of POCUS during triage evaluation. The ED triage process was performed as recommended by the hospital guidelines or by including a nurse-performed POCUS evaluation. Only urgent or less codes were considered eligible for the study. The timing of all evaluations was recorded along with the opinion of the nurses involved in the study on the impact of POCUS results on the triage process. After ED discharge, the most appropriate triage code was determined by independent review of the triage data.Results: A total of 312 patients were enrolled, 101 of whom were evaluated with the hospital standard triage process. Nine nurses with expertise in both ED triage and POCUS were involved in the study. The majority of the enrolled patients were deferrable or minor urgency (about 60% in both groups). The median time needed for the triage evaluation was 180 seconds (range 540), 90 seconds longer in the POCUS group than in the standard triage group (p